Resolution of Failed Banks by Deposit Insurers : Cross-Country Evidence - Beck, Thorsten; Laeven, Luc (World Bank, Washington, DC, 2012)
There is a wide cross-country variation in the institutional structure of bank failure resolution, including the role of the deposit insurer. The authors use quantitative analysis for 57 countries and discuss specific country cases to illustrate this variation. Using data for over 1,700 banks across 57 countries, they show that banks in countries where the deposit insurer has the responsibility of intervening failed banks and the power to revoke membership in the deposit insurance scheme are more stable and less likely to become insolvent. Involvement of the deposit insurer in bank failure resolution thus dampens the negative effect that deposit insurance has on banks' risk taking.